Post Keynesian econometrics, microeconomics and the theory of the firm : beyond Keynes, volume 1 - Hillard, John, 1946-; Dow, Sheila C. (Cheltenham ; Northampton, MA : E. Elgar, 2002)
This is the first of two volumes celebrating Keynes' contribution to economics and the development of post-Keynesian economics in recent years. The book is divided into three sections - general issues, uncertainty and international economics.
Includes bibliographical references and index.
oif 17/04/15
Loan
Keywords: Keynes, John Maynard, -- 1883-1946.; Microeconomics; Keynesian economics; Corporations; Econometrics